Studies on Meliolaceae of India-IV - S.H. MAHAMULKAR, M.S. PATIL and (Indian Phytopathology, 2002)
Thirty seven taxa (27 species and 10 varieties) belonging to seven genera (Amazonia (2 spp.), Appendiculella (2 spp.), Asteridiella (4 spp. and 2 varieties), Armatella (one sp.), Irenopsis (3 spp. and one variety), Meliola (14 spp. and seven varieties) and Ophioirenina (one sp.)) of the family Meliolaceae are described and illustrated. Out of these 37 taxa, five species (Asteridiella theae, Irenopsis ligustri, I. nephelii, I. rubi and Meliola dimorphochaeta) and two varieties (Meliola celticola var. indica and M. setariae var. indica) have been proposed as new, and nine species (Appendiculella gloriosa, Asteridiella atricha, A. tremae, A. tarlacensis, Meliola anodendrae, M. banosensis, M. longiseta, M. mammeicola and M. vitis) are new additions tothe fungi of India: the genus Ophioirenina has been recorded for the first time from India; two new reported species of Meliola have been revised as synonyms while the remaining 19 taxa, which are either new to the states or collected on hitherto, unreported hosts, are only listed. A key to the genera of Indian Meliolaceae is also provided.